Predictors of Severity and Management of Severe Leptospirosis Patients in Intensive Care Unit - Kusumawardani, Dwi Indriati; Jufan, Akhmad Yun (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2025)
Background: Severe leptospirosis or Weil's syndrome occurs in 10% of leptospirosis cases, with a mortality rate of 5-40%. Misdiagnosis of leptospirosis often occurs due to nonspecific symptoms. Discussion of risk factors, causative agents, pathogenesis, clinical manifestations, diagnostic techniques, and predictors of disease severity are crucial for successful management.Cases: We report 3 cases of leptospirosis with various clinical manifestations and management. In these 3 cases, older age was associated with severe leptospirosis and poor outcomes. The SPiRO score can identify patients with severe leptospirosis requiring intensive care. All three cases of leptospirosis were severe with complications in the kidneys, lungs, and hematological system requiring intensive care in the intensive care unit (ICU).Discussion: Early and appropriate management can reduce patient mortality rates. ICU management of leptospirosis includes antibiotics, fluid balance, and support for affected organs. Patients with respiratory failure are given oxygenation using high-flow nasal cannula (HFNC), non-invasive ventilation (NIV), or invasive mechanical ventilation with endotracheal intubation (ETT). Acute kidney failure in leptospirosis can be managed with hemodialysis as indicated or may improve with conservative therapy. Corticosteroids may be administered for thrombocytopenia associated with leptospirosis.Conclusion: The three cases of leptospirosis were severe with complications in the kidneys, lungs, and hematological system requiring intensive care in the ICU. Early and appropriate management can reduce patient mortality rates. In these 3 cases, older age, mechanical ventilation, acute kidney failure, septic shock, thrombocytopenia, and elevated transaminase enzymes were associated with severe leptospirosis and poor outcomes.